Graphene synthesis and antibody immobilization techniques for iImmunosensors - Shohibuddin, Ihda Uswatun Shalihah; Barthasarathy, Piravin Raj; Wan Salim, Wan Wardatul Amani (Springer Singapore, 2020)
The principle of antigen–antibody interaction is exploited for immunosensor development. Over the years, immunosensors have been fabricated for different applications, and the fabrication process has benefited from the use of nanomaterials. Graphene, a single-atom-thick layer of carbon, has been used to coat the sensing electrodes of immunosensors; antibodies are then immobilized onto the graphene-modified electrodes to produce graphene-based immunosensors. Here, we describe several techniques for producing graphene and its derivatives. We also focus on approaches for antibody immobilization on these graphene-modified electrodes.